Expert PID control system for blood glucose control in critically ill patients. - Chee, F.
In this paper, the design of an expert proportional-integral-derivative (PID) control system for blood glucose regulation in patients, such as the intensive care population, is described. The control system applied the concept of expert system, and proportional, integral and derivative control in clinical sliding table technique, to effect a control algorithm in the form of an "active" sliding table that is used to prescribe insulin infusion rates. This combination provided dynamic properties to the sliding table control. Clinical results have shown a comparable performance between the control system and routine clinical treatment, in terms of blood glucose level maintained. Nevertheless, the control system is sensitive to sensor reading artefact, particularly in the lower ranges of blood glucose level, mandating manual intervention.
Keywords: ANCOVA; Active sliding table; Blood glucose control; Bolus giving mechanism; Clinical sliding table technique; Closed-loop control system; Control algorithm; Critically ill patients; Expert PID control system; Hourly scheduling part; Insulin infusion rates; Intensive care; Least square regression; Sensor reading artefact